Romance "A Hora da Estrela", de Clarice Lispector:: Reflexões sobre violência de gênero no Brasil - Menezes Souto, Gisleule Maria; Mathias Souto, Luana (Language and Law / Linguagem e Direito, 2022)
The interdisciplinary relationship between Law and Literature allows jurists to expand their understanding of the world. The realities and their consequences are not always clear, it’s often veiled, subtle and for this reason, in order to understand the reality of gender-based violence in Brazil, this article will engage a dialogue with the novel 'The Hour of Star' by Clarice Lispector. The objective is to present the different nuances for which gender-based violence occurs and through a bibliographic, legislative and empirical data review conclude how this interdisciplinary relationship can assist in the understanding and creation of more effective normative instruments for its punishment.